Does physical training reduce fatigue in sarcoidosis? - Marcellis, Rik; van der Veeke, Melanie; Mesters, Ilse; Drent, Marjolein; de Bie, Rob; de Vries, Geeuwke; Lenssen, Antoine (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Sarcoidosis patients frequently experience fatigue, exercise intolerance and muscle weakness, resulting in reduced quality of life (QOL). Scientific studies on the benefits of physical training in sarcoidosis have been scarce, so the aim of this pilot study was to examine the impact of a 13-week physical training program on fatigue, physical functions and QOL in fatigued sarcoidosis patients and/or patients with exercise intolerance. Methods: 18 sarcoidosis patients participated in a 13-week physical training program. The Fatigue Assessment Scale (FAS), World Health Organization Quality of Life-BREF assessment instrument (WHOQOL-BREF),Medical Research Council (MRC) dyspnea scale, Visual Analogue Scale (VAS), six-minute walk test (6MWT), submaximal bicycle test and muscle strength of the quadriceps and elbow flexors were assessed at baseline and after the program. Results: FAS scores had decreased (mean difference -2.7 points, 95% CI -4.4 to -1.1) after completion of the training program, along with improvements in WHOQOLBREF psychological health domain (mean difference 0.9 points, 95% CI 0.2 to 1.7) and MRC dyspnea score (mean difference -0.4 points, 95% CI -0.8 to -0.1). 6MWD improved by 34.6 m (95% CI 20.3 to 49.0) and mean heart rate on the bicycle test improved (mean difference 8.4 beats/minute, 95% CI -13.8 to -3.0), as did quadriceps strength (mean difference 10.7 kg, 95% CI 5.5 to 15.9). Conclusion: Fatigue reduced after a period of physical training in sarcoidosis patients. Moreover, psychological health and physical functions improved. Future studies are warranted to assess the benefits of physical training in sarcoidosis.